2012
DOI: 10.4049/jimmunol.1103129
|View full text |Cite
|
Sign up to set email alerts
|

Host Factor Transcriptional Regulation Contributes to Preferential Expression of HIV Type 1 in IL-4–Producing CD4 T Cells

Abstract: HIV-1 replicates preferentially in IL-4 producing CD4 T cells for unclear reasons. We show increased HIV-1 expression is irrespective of viral tropism for chemokine receptors as previously suggested, but rather transcription of the HIV-1 long terminal repeat (LTR) is increased in IL-4 producing CD4 T cells. Increased expression of HIV-1 message is also confirmed in IL-4 producing CD4 T cells from HIV-1 infected individuals ex vivo. In exploring a transcriptional mechanism, we identify a novel c-maf (required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…The core sequence for NFAT binding is GGAAA (38,39). Of the NFAT family members, the NFAT1 homodimer can occupy the complementary sequence of 5 bp in the 3= half of the H-B motif (GGGACTTTCC; the NFAT binding sequence within the H-B motif is underlined) and modulate HIV-1 gene expression (40,41). Due to a partial overlap in the H-B motif, NFAT and NF-B could compete, leading to the mutually exclusive binding and alternate transactivation by these two factors (42).…”
Section: Resultsmentioning
confidence: 99%
“…The core sequence for NFAT binding is GGAAA (38,39). Of the NFAT family members, the NFAT1 homodimer can occupy the complementary sequence of 5 bp in the 3= half of the H-B motif (GGGACTTTCC; the NFAT binding sequence within the H-B motif is underlined) and modulate HIV-1 gene expression (40,41). Due to a partial overlap in the H-B motif, NFAT and NF-B could compete, leading to the mutually exclusive binding and alternate transactivation by these two factors (42).…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of the study reported here, the difference between T-bet expression in HIC and viremic patients stems from the negative correlation between T-bet and CD38þ expressions in CM CD4þ T cells, suggesting that HIC have an expanded Th1 CM CD4þ T cell population expressing fewer CD38 molecules at their surface. This population could contribute to HIC viral control since it may produce less IL-4 than CD4þCD38 high in response to HIV peptides, and restrict HIV-1 replication [39,40]. In other words, the ratio between Tbet and CD38 could be a predominant characteristic that determines the efficiency of CM CD4þ T cells in HIC.…”
Section: Discussionmentioning
confidence: 96%
“…However, viral reactivation in response to TCR-induced signals follows a stochastic pattern (16,27), implying that clonal expansion can at least sometimes occur in the absence of viral reactivation. Whether the efficacy of viral reactivation in functionally polarized cells is influenced by signature transcription factors of polarized T cells is currently unknown; however, it is noteworthy that GATA-3 and c-Maf, two transcription factors involved in regulating Th2-polarization, can stimulate HIV-1 expression through direct interactions with the HIV-1 promoter (28,29); this may facilitate immune-mediated clearance of HIV-1-infected Th2 cells and correspond to the very low frequency of clonally-expanded Th2 cells encoding intact HIV-1 in our study. Interestingly, TCR-independent homeostatic proliferation can drive HIV-1-infected cell proliferation in the absence of viral reactivation (30), at least in in vitro experiments, but this mechanism may possibly account for a smaller proportion of clonal turnover in T cells, relative to antigen-driven T cell proliferation.…”
Section: Discussionmentioning
confidence: 99%